Cyclospora and cyclosporiasis : epidemiology, diagnosis, detection, and control - Zhang, Long-Xiang; Wang, Rong-Jun; Zhao, Guang-Hui; Li, Jun-Qiang (Academic Press, 2021)
Cyclospora cayetanensis is a microscopic parasite that can be transmitted via food or water sources and causes intestinal disease (Cyclosporiasis) in humans. Cyclospora and Cyclosporiasis: Epidemiology, Diagnosis, Detection, and Control reviews 22 species of Cyclospora and discusses C. cayetanensis infection in humans. This book offers comprehensive coverage that includes taxonomy and biology, molecular characteristics, and transmission of the parasite. It also provides researchers, clinicians, public health officials, and food safety officials with basic data for the epidemiology of the Cyclospora spp. or C. cayetanensis, as well as strategies to monitor large-scale outbreaks of Cyclospora spp. or C. cayetanensis. The book further covers clinical symptoms, diagnostic methods, and means of treatment and prevention of this disease and informs readers of the hazards of the parasite, common means of transmission, and self-protection measures.